A Comparison of Physical Activity Between Home-Based and Centre-Based Pulmonary Rehabilitation: A Randomised Controlled Secondary Analysis - Horton, Elizabeth J.; Ruksenaite, Justina; Mitchell, Katy; Sewell, Louise; Newby, Christopher; Singh, Sally J. (Frontiers in Rehabilitation Sciences, 2021)
Background: Pulmonary Rehabilitation (PR) is a highly effective intervention for individuals with chronic obstructive pulmonary disease (COPD). Physical activity (PA) has been shown to increase after centre-based programme, yet it is not clear if home-based programme can offer the same benefit. The aim of this study was to evaluate the effect of home-based PR compared to centre-based PR on PA levels post seven weeks of PR and six months follow up. Method: Fifty-one participants with COPD (36 male) completed physical activity monitoring with a SenseWear Armband, at three time points. Participants were randomly assigned to either centre-based supervised PR (n=25; 69 ± 6 yr; FEV1 55 ± 20% predicted) or home-based PR (n=26; 68 ± 7 yr; FEV1 42 ± 19% predicted) programmes lasting seven weeks. The home-based programme including one hospital visit, a self-management manual and 2 telephone calls. PA was measured as step count, time in moderate PA (3-6 METs) in bouts of 10 plus minutes and sedentary time (< 2 METs). Results: Home-based PR increased step count significantly more than centre-based PR after seven weeks (mean difference 1463 steps: 95% CI 280 to 2645, p=0.02). No different in time spent in moderate PA was observed (mean difference 62 mins: 95% CI –56 to 248, p=0.24). Sedentary behaviour was also significantly different between centre and home-based groups. The home group spent 52 min less time sedentary compared to centre-based (CI -106 to 2, p = 0.039). However, after 6 months step count and time spent in moderate PA returned to baseline in both groups. Conclusion: This study provides an important insight into the role of home-based PR which has the potential to be offered as an alternative to centre-based PR. Understanding who may best respond to either centre or home-based PR warrants further exploration and how to maintain these initial benefits long term